The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1155/2012/501979
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Depression: Main Phenomenological Clusters and their Relationships with Clinical Measures

Abstract: Abstract. Objectives:To investigate the principal psychopathological dimensions of post-stroke depression (PSD) through the assessment of the factorial structure of the Post-Stroke Depression Rating Scale (PSDRS). Methods: We enrolled ninety-eight subjects with PSD, who underwent the PSDRS, MMSE and Barthel Index. Information about demographic, clinical, and neuroanatomical factors was collected.Results: The factor analysis extracted three factors accounting for 63.4% of the total variance, and identified as: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Since the behavior of our aged rodents was more „apathetic“ we hypothesize that the increased HT2B mRNA and protein expression in neurons around the peri-lesional area was due to the interruption of asceding inputs from basal ganglia which normally supply neurons in the frontal cortex with biogenic amines like 5-HT and dopamine. Our hypothesis is supported by animal studies reporting an upregulation of Htr2B mRNA and protein in response to the serotonergic deafferentation to compensate for the loss of serotonin input [ 55 ] and several clinical studies in elderly patients that reported an association between old age and apathy in stroke survivors [ 42 , 56 , 57 ] and normal elderly subjects [ 51 ]. Furthermore, apathy is significantly more represented in late onset depression than in early onset depression [ 58 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Since the behavior of our aged rodents was more „apathetic“ we hypothesize that the increased HT2B mRNA and protein expression in neurons around the peri-lesional area was due to the interruption of asceding inputs from basal ganglia which normally supply neurons in the frontal cortex with biogenic amines like 5-HT and dopamine. Our hypothesis is supported by animal studies reporting an upregulation of Htr2B mRNA and protein in response to the serotonergic deafferentation to compensate for the loss of serotonin input [ 55 ] and several clinical studies in elderly patients that reported an association between old age and apathy in stroke survivors [ 42 , 56 , 57 ] and normal elderly subjects [ 51 ]. Furthermore, apathy is significantly more represented in late onset depression than in early onset depression [ 58 ].…”
Section: Discussionsupporting
confidence: 69%
“…The pattern of brain distribution suggests that the activation of 5-HT2 receptor subtypes may be implicated in the regulation of mood disorders [ 42 ]. Indeed we found that Htr2B mRNA but not Htr2A mRNA, was robustly increased in the perilesional frontal area of aged rats suggesting that the interruption in the serotoninergic innervation of cortical neurons by stroke may lead to an increased expression of Htr2B mRNA and serotonin receptors in the motor and frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PSD exhibit poor rehabilitation outcomes, social isolation, suicidal ideation, and suicide attempts, all of which affect recovery, prolong hospital stays and increase the economic burden compared to non-depressed stroke patients (Cai et al, 2019). With the physiological defect and social dysfunction, PSD also causes cognitive impairments such as attentional decline, impaired memory, and impaired motor function (Quaranta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PSD might be associated with the impairment of other neurological functions such as learning, executive, and motor functions. Most importantly, PSD could negatively influence the functional outcome after stroke rehabilitation and is a risk factor for low quality of life after stroke and a high morbidity [2, 3]. …”
Section: Introductionmentioning
confidence: 99%